Pengamatan Kadar Senyawa Polisiklik Aromatik Hidrokarbon (PAH): Benzo (a) Pyrene, Benzo (a) Anthracene, Benzo (b) Fluoranthene, di-Benzo (a,h) Anthracene, dan Benzo (g,h,i) Perylene dalam Air Laut di Teluk Jakarta - Edward (Pro-Life, 2021)
Measurement of the concentration of polycyclic aromatic hydrocarbons (PAHs) compounds Benzo(a) Pyrene, Benzo(a)Anthracene, Benzo(b)Fluoranthene, Di-benzo(a,h)Anthracene, and Benzo(g,h,i) Perylene in seawater in Jakarta Bay was conducted in July-August 2015. The purpose of this study is to determine the level of pollution of five PAH compounds in seawater in their relation to the protection of marine organisms. Seawater samples were taken by using a water sampler at 23 research stations. The station position is determined by using the Geographical Position System (GPS). All samples were analyzed by using Gas Chromatography. The results showed that the concentration of the five PAH compounds in seawater in the western parts of Jakarta Bay was higher than the middle and the eastern parts. The content of the five PAHs compounds is still in accordance with the safe threshold value for marine organism life.